The Correlation between Diabetes Mellitus and Mild Cognitive Impairment in the Elderly in Surakarta - Immanuel Billy Brilliandi; Rivan Danuaji; Bhisma Murti (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Introduction: Mild cognitive impairment one of DM complication. The main factor leading to mild cognitive impairment is the alteration of the white matter of the brain. Impaired cognitive patients with DM causing great suffering for the patient themselves, their families, and their surrounding neighborhood and environment. The main objective of the study is to determine the correlation between DM and mild cognitive impairment in the elderly in Surakarta. Methods: This study is an analytic observational study with cross-sectional approach. The study was held in Dr. Moewardi General Hospital of Surakarta and Puskesmas Ngoresan. The independent variable was DM and the dependent one was mild cognitive impairment. The result of the study was analyzed by chi-square test and multiple logistic regression test. Result: The subjects were divided into two groups, the first one was a group of 22 people with DM and the other consisted of 23 people without DM. The subjects were directly asked to fill up the Montreal Cognitive Assessment-Indonesian version (MOCA-Ina) for the assessment of their cognitive function. The result of Chi-square test showed that DM and years of education were the variables which had the correlation with mild cognitive impairment (p= 0,003 and p= 0,020). The result of multiple logistic regression test showed that diabetes mellitus was the only one factor which had the correlation with mild cognitive impairment statistically (OR=5,489; CI 95%= 1,438 20,949; p= 0,013). Conclusions: There was a positive correlation between DM and mild cognitive impairment in the elderly in Surakarta. Keywords: Diabetes mellitus, mild cognitive impairment, neurobehavior, MOCA-Ina, elderly.